Evaluating the Validity, Practicality, and Effectiveness of a Flipbook-Based E-Module on Bacteria for Tenth-Grade Students - Ramadansur, Rahmat; Sutomo, Edi; Syahdan, Syahdan; Siswati, Bea Hana; Umarella, Melati. I. S. (Biosfer: Jurnal Tadris Biologi, 2026)
This study evaluated the validity, practicality, and effectiveness of a flipbook-based e-module for teaching bacteria to tenth-grade students. The study used a research and development design with the 4D model: define, design, develop, and disseminate. Participants included 90 students from experimental and control classes and six expert validators. Data were collected using validation sheets, response questionnaires, and pretest and posttest instruments. The results showed that the e-module was highly valid in terms of content, language, and media quality. Teacher and student responses indicated that the module was practical, attractive, and easy to use. Students who used the flipbook e-module achieved better learning outcomes than those taught with conventional materials. These findings indicate that interactive digital media can strengthen students’ understanding of bacteria and support more active biology learning. Mengevaluasi Validitas, Kepraktisan, dan Efektivitas Modul Elektronik Berbasis Flipbook tentang Bakteri untuk Siswa Kelas Sepuluh ABSTRAK: Penelitian ini mengevaluasi validitas, kepraktisan, dan efektivitas e-modul berbasis flipbook pada materi bakteri untuk siswa kelas X. Penelitian menggunakan desain penelitian dan pengembangan dengan model 4D, yaitu define, design, develop, dan disseminate. Subjek penelitian terdiri atas 90 siswa pada kelas eksperimen dan kontrol serta enam validator ahli. Data diperoleh melalui lembar validasi, angket respons, serta instrumen pretest dan posttest. Hasil penelitian menunjukkan bahwa e-modul sangat valid pada aspek materi, bahasa, dan media. Respons guru dan siswa menunjukkan bahwa e-modul praktis, menarik, dan mudah digunakan. Siswa yang menggunakan e-modul memperoleh hasil belajar lebih baik daripada siswa yang belajar dengan bahan konvensional. Temuan ini menunjukkan bahwa media digital interaktif dapat memperkuat pemahaman konsep bakteri dan mendukung pembelajaran biologi yang lebih aktif.